Leader empowering behaviour: relationships with nurse and patient outcomes. Issue 4 (28th September 2020) - Cziraki, Karen; Wong, Carol; Kerr, Michael; Finegan, Joan
Abstract : Purpose: This study aims to test a model examining the impact of leader empowering behaviour on experienced nurses' self-efficacy, interprofessional collaboration, job turnover intentions and adverse patient outcomes. Design/methodology/approach: Structural equation modelling in Mplus was used to analyse cross-sectional survey data from experienced nurses in Alberta, Ontario, and Nova Scotia, Canada ( n = 478). Findings: The results supported the hypothesized model: (164) = 333.021, p = 0.000; RMSEA = 0.047; CFI = 0.965; TLI = 0.959; SRMR = 0.051. Indirect effects were observed between leader empowering behaviour and nurses' assessment of adverse events and leader empowering behaviour and nurses' job turnover intentions through interprofessional collaboration. Research limitations/implications: Leader empowering behaviour plays a role in creating collaborative conditions that support quality patient care and the retention of experienced nurses. Practical implications: The findings will be of interest to academic and hospital leaders as they consider strategies to retain experienced nurses, such as nurse manager selection, development and performance management systems. Originality/value: The influx of new graduate nurses to the nursing profession and changing models of care requires the retention of experienced nurses in the workforce. The findings suggest that leader empowering behaviour and interprofessional collaboration are important factors in supporting quality patient care and stabilizing the nursing workforce.